If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6y + 6z = -10 Solving 2x + -6y + 6z = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 2x + -6y + 6y + 6z = -10 + 6y Combine like terms: -6y + 6y = 0 2x + 0 + 6z = -10 + 6y 2x + 6z = -10 + 6y Add '-6z' to each side of the equation. 2x + 6z + -6z = -10 + 6y + -6z Combine like terms: 6z + -6z = 0 2x + 0 = -10 + 6y + -6z 2x = -10 + 6y + -6z Divide each side by '2'. x = -5 + 3y + -3z Simplifying x = -5 + 3y + -3z
| 8d-(2-3d)=42 | | 1/3-9=12 | | 52.0-7.2x= | | -2.5(6)= | | 2x+4+3x+3=29 | | 3.2x+20.8= | | 28-10x+2x^2=8+4x | | 8d-0.333(6-9d)=42 | | 9x4-6/5(5-4) | | ln(x+4)=10 | | X^3-3x^2-116=0 | | 12x+5=5x-4 | | 10d-3d=20+1 | | 15x-80+61=46 | | 4x^2+74x-210=0 | | 25-x=72 | | 4x^2+74x+210=0 | | (x*x)+3x=5 | | 5a+12=18 | | x^3y^2+x^2y-42x= | | -2=8-x | | xx+3x-5=6 | | 4x^21=0 | | (-5*(-1(-1*b)))+(-5*b)=3 | | (-5*(-1-1b))+(-5*b)=3 | | 7n=8m | | (-5*(-1+(-1b)))+(-5*b)=3 | | 2x=25+9 | | 14x=x-29 | | 18x^2+6x-21=0 | | -5*(-1+(-1b))+(-5*b)=3 | | 2w+10-8=-38 |